Seroprevalence of human brucellosis in Travnik, Central Bosnia and Herzegovina - Bacic, Azra; Todorovac, Emina; Asotic, Jasminka; Prazina, Nedzad (Technium BioChemMed, 2024)
Objectives: To measure and analyze the seroprevalence and risk factors of human brucellosis among clinically suspected patients in the Travnik area, Bosnia and Herzegovina in the period 2018-2023. Methods: A total of 337 samples of clinically suspected brucellosis patients in Travnik, Central Bosnia and Herzegovina were collected between 2018-2023. Rose Bengal agglutination was used for sera testing. Expressive and investigative statistics were considered. Differences between the prevalence of brucellosis according to age, sex, and the seasonal incidence rate were assessed. Results: The prevalence of brucellosis among the suspected patients was 23.30%. The highest prevalence rate 35.71%, was detected during year 2021. Higher rate of brucellosis was observed among males 63.86% than females 36.14%. Most cases were reported during month of June and October, 14.15% and 14.19% respectively. The highest prevalence, 56.76% rate was observed in age group 41–60 years old. Conclusion: Our survey found a high prevalence of human brucellosis among clinically suspected patients in Travnik area strongly indicating that clinical suspicion is a valid criterion, which requires fast laboratory detection and patient treatment. Detecting specific anti-Brucella antibodies using agglutination Rose Bengal test is a fast a reliable diagnostic procedure for clinically suspect individuals. There is a strong association between human brucellosis and age.